Dopamine-regulated MicroRNA MiR-181a controls GluA2 surface expression in hippocampal neurons - Saba, Reuben; Störchel, Peter H.; Aksoy Aksel, Ayla; Kepura, Frauke; Schratt, Gerhard (Molecular and cellular biology, 2012)
The dynamic expression of AMPA-type glutamate receptors (AMPA-R) at synapses is a key determinant of synaptic plasticity, including neuroadaptations to drugs of abuse. Recently, microRNAs (miRNAs) have emerged as important posttranscriptional regulators of synaptic plasticity, but whether they target glutamate receptors to mediate this effect is not known. Here we used microarray screening to identify miRNAs that regulate synaptic plasticity within the nucleus accumbens, a brain region critical to forming drug-seeking habits. One of the miRNAs that showed a robust enrichment at medium spiny neuron synapses was miR-181a. Using bioinformatics tools, we detected a highly conserved miR-181a binding site within the mRNA encoding the GluA2 subunit of AMPA-Rs. Overexpression and knockdown of miR-181a in primary neurons demonstrated that this miRNA is a negative posttranscriptional regulator of GluA2 expression. Additionally, miR-181a overexpression reduced GluA2 surface expression, spine formation, and miniature excitatory postsynaptic current (mEPSC) frequency in hippocampal neurons, suggesting that miR-181a could regulate synaptic function. Moreover, miR-181a expression was induced by dopamine signaling in primary neurons, as well as by cocaine and amphetamines, in a mouse model of chronic drug treatment. Taken together, our results identify miR-181a as a key regulator of mammalian AMPA-type glutamate receptors, with potential implications for the regulation of drug-induced synaptic plasticity.